A pandemic grant package for the world's poorest economies: Not as costly as you might think, but too costly to happen anytime soon - Steven B. Kamin; Ben Clements (American Enterprise Institute (AEI), 2020)
The emerging-market and developing economies face a multitude of grave challenges as they confront the COVID-19 pandemic, including a critical lack of budgetary space. Observers have highlighted the need to bolster the international financial institutions' lending capacity in the event of a "sudden stop" in global capital flows such as occurred in March.
Keywords: A; 330; Budget deficit; Coronavirus; Fiscal policy; grants; Gross Domestic Product GDP; International economy; International Monetary Fund IMF